Retensi Antosianin dari Ekstrak Daun Bayam Merah (Alternanthera amoena Voss) pada Pengolahan Mie Basah: Retention of Anthocyanin from Red Spinach Leaves Extract (Alternanthera amoena Voss) in Processing Wet Noodles - Betzy Eppang; Nurhaeni; Khairuddin; Ahmad Ridhay; Jusman (KOVALEN: Jurnal Riset Kimia, 2020)
Research about the retention of red spinach leaves extract (Alternanthera amoena Voss) as a natural coloring and preservative in wet noodles has been done. The study aim is to determine the anthocyanin retention of red spinach leaves extract in the processing of wet noodles and determine the organoleptic quality of wet noodles by adding pigment red spinach leaves extract. The extraction method used the maceration method by ethanol solvent. Anthocyanin levels on an extract that obtained by using a UV-Vis spectrophotometer were 33.34%. Anthocyanin retention of red spinach leaves extract on wet noodle processing at storage times of 0, 6, 12, 18, 24, 30, 36, 42, and 48 hours was 100%, 75.87%, 75.37%, 74.95%, 74.62%, 74.12%, 73.28%, 71.70%, and 70.61%. Organoleptic quality of wet noodles that was added with extract has “like” to “really like” grade with score detail of the best color of 4.37 at 18 hours storage, whereas the odor, texture, and taste for 0 hours storage have the highest score of 4.63, 4.63, and 4.57, respectively. The wet noodles with red spinach leaves extract more preferred than the noodles without extracts. Keywords: Retention, anthocyanin, Alternanthera amoena Voss., wet noodles